Історичний розвиток інституту видачі особи (екстрадиції) в Україні - Саско, О; Крикунов, О; Sasko, O; Krykunov, A (СНУ ім.Лесі Українки, 2019)
У статті простежено процес становлення та розвитку інституту видачі осіб, які вчинили злочини. Авторами розглянуто основні етапи і закономірності розвитку екстрадиційних відносин і їх правові основи. Зроблено висновки про те, що історія розвитку інституту видачі осіб, які вчинили кримінальні правопорушення, охоплює практично всі історичні етапи розвитку суспільства. Проте лише в наш час екстрадиція набула всесвітнього значення відносно злочинів міжнародного характеру і злочинів проти миру і безпеки людства. Інститут екстрадиції як сукупність норм матеріального і процесуального характеру, а також в основі якого лежать договірні норми (у чому і його особливість), становить собою упорядковану на основі права форму міждержавної співпраці, орієнтовану на підтримку міжнародної законності й правопорядку. The article elucidates the process of formation and development of the institution for the extradition of persons who committed crimes. It examines the main stages and patterns of development of extradition relations and their legal foundations. The institute of Extradition, as a set of norms of material and procedural nature and the basis of which are contractual norms (it is its peculiarity), is an orderly form of international cooperation focused on the support of international legality and law. The history of the institution of the extradition of persons who committed criminal offenses development covers almost all historical stages of society's development. However, only in our time, the extradition concerning the crimes of the international character and crimes against the peace and security of mankind has gained universal importance. The study has revealed legislative gaps that may complicate the implementation of paragraphs 2, 3, part 9 of article 588 of the Criminal Procedural Code, since the legislator has not clearly identified the grounds for refusing extradition in a simplified manner. This may lead to unsubstantiated refusals in the extradition of offenders issued by the authorized central body of Ukraine.
Institution of Extradition in Ukraine: History of Development
Keywords: екстрадиція; видача правопорушників; розвиток екстрадиції; міжнародне співробітництво; екстрадиційні відносини; extradition; extradition of criminals; extradition development; international cooperation; extradition relations